The importance of mentors and how to handle more than one mentor. Issue 1 (21st April 2022) - Marshall, Andrea G; Brady, Lillian J; Palavicino-Maggio, Caroline B; Neikirk, Kit; Vue, Zer; Beasley, Heather K; Garza-Lopez, Edgar; Murray, Sandra A; Martinez, Denise; Shuler, Haysetta D; Spencer, Elsie C; Morton, Derrick J; et al.
Abstract: Working with multiple mentors is a critical way for students to expand their network, gain opportunities, and better prepare for future scholastic or professional ventures. However, students from underrepresented groups (UR) are less likely to be mentored or have access to mentors, particularly in science, technology, engineering, and mathematics (STEM) fields. We developed and implemented a workshop, to provide the necessary foundation for students to be better prepared for establishing future mentorships throughout graduate and professional school. Faculty well-versed in the area of effective mentorship from multiple universities developed and delivered a 1.5-hour workshop to address the roles of a mentor, especially when it comes to UR students, and how students may effectively work with multiple mentors. This workshop was delivered to a group of students from, the Historically Black College and University (HBCU), Winston-Salem State University, and a pre/post-10-point Likert scale-based survey was administered where 1 represented strongly disagree and 10 was strongly agree. The questions used in this seminar were newly designed by the authors as program evaluations. We analyzed the raw data with nonparametric tests for comparison within paired samples. Wilcoxon matched-pairs and signed-rank tests showed statistically significant growth in student self-ratings related to the workshop learning objectives. The 'How to Handle More than One Mentor to Achieve Excellence' workshop was well-received as a component of pregraduate and preprofessional training. Incorporating workshops like this may increase student preparedness around developing and cultivating healthy mentorship relationships throughout STEM training. Abstract : This contribution reports the outcome of a workshop focused on increasing student preparedness around developing and cultivating healthy mentorship relationships throughout STEM training.